A Revolutionist Analysis of The Thirty-Year Authoritarian Rule of Hosni Mubarak in Egypt (Journal of Social Sciences Review, 2024)
This study aims to analyze the Egyptian revolution and the subsequent overthrow of the long-standing authoritarian leader, Hosni Mubarak. The text emphasizes the youth of Egypt's part in changing the dictatorship to establish democracy in the country. This paper emphasizes the reasons that motivated the Egyptians to leave their homes and overthrow Hosni Mubarak. The investigation also includes the excessive use of authority by state officials to suppress protests. This research also examines the involvement of the military and other law enforcement agencies during the revolution. The text delves into the utilization of social media during the protests and its role in disseminating information about the events. This document briefly discusses the previous authoritarian leaders of Egypt, including Hosni Mubarak. The text also delves into the strategies employed by authoritarian regimes to extend their reigns.
Keywords: Egypt; Hosni Mubarak; Social Media; Protest; Revolution